Evidence‐based dentistry skill acquisition by second‐year dental students. (22nd May 2018) - Marshall, T. A.; McKernan, S. C.; Straub‐Morarend, C. L.; Guzman‐Armstrong, S.; Marchini, L.; Handoo, N. Q.; Cunningham, M. A.
Abstract: Introduction: Identification and assessment of Evidence‐based dentistry (EBD) outcomes have been elusive. Our objective was to describe EBD skill acquisition during the second (D2) year of pre‐doctoral dental education and student competency at the end of the year. Methods: The first and fourth (final) curricular‐required EBD Exercises (ie, application of the first 4 steps of the 5‐Step evidence‐based practice process applied to a real or hypothetical situation) completed by D2 students (n = 151) during 2014‐2015 and 2015‐2016 were evaluated to measure skill acquisition through use of a novel rubric with measures of performance from novice to expert. Exercises were evaluated on the performance for each step, identification of manuscript details and reflective commentary on manuscript components. Changes in performance were evaluated using the chi‐square test for trend and the Wilcoxon signed‐rank test. Results: Seventy‐eight per cent of students scored competent or higher on the Ask step at the beginning of the D2 year; scores improved with 58% scoring proficient or expert on the fourth Exercise ( P < .001). Most students were advanced beginners or higher in the Acquire, Appraise and Apply steps at the beginning of the D2 year, with minimal growth observed during the year. Identification of manuscript details improved between the first and fourth Exercises ( P = .015); however, depth of commentary skills did not change. Discussion: Unlike previous investigations evaluating EBD knowledge or behaviour in a testing situation, we evaluated skill acquisition using applied Exercises. Conclusion: Consistent with their clinical and scientific maturity, D2 students minimally performed as advanced beginners at the end of their D2 year.